Natural orifice specimen extraction in laparoscopic colorectal cancer surgery: A case series study. (January 2021) - Masubuchi, Shinsuke; Okuda, Junji; Yamamoto, Masashi; Inoue, Yoshihiro; Tanaka, Keitaro; Uchiyama, Kazuhisa
Highlights: Now that laparoscopic surgery is widespread, minimally invasive surgery is desired. Natural orifice specimen extraction is minimally invasive surgery. Transanal specimen extraction and transvaginal specimen extraction. Natural orifice specimen extraction appears to be feasible and safe. Abstract: Introduction: In recent years, natural orifice specimen extraction (NOSE) has been attracting attention as a further minimally invasive operation for colorectal cancer, and not only improvement of appearance, but also reduction of pain and wound-related complications due to abdominal wall destruction has been reported. However, NOSE is technically complicated and difficult, and it has not yet been widely used. The aim of this study was to confirm the feasibility, safety, and short-term outcomes of total laparoscopic colon cancer surgery with NOSE. Case presentation: From May 2018 to October 2019, eight patients with stage 0 or I colon cancer underwent NOSE surgery in our hospital. Transanal specimen extraction was performed in six cases, and transvaginal specimen extraction was performed in two cases. All operations were successfully accomplished without conversion to open surgery. The anastomosis method was double stapling technique in three cases and overlap method in five cases. The median operative time was 224 min. The median blood loss was 10 mL. The median time to first flatus was 1 day, and the median time to first stool was 2 days. The median postoperative observation period was 18 months, but there was no recurrence. There were no postoperative complications in these cases. Conclusion: Total laparoscopic colon cancer surgery with NOSE appears to be feasible, safe, and show promising efficacy for selected patients.